Antioxidant and hypoglycemic activities of extract and fractions of Rambutan seeds (Nephelium lappaceum L.) - Sylvia Soeng; Endang Evacuasiany; Wahyu Widowati; Nurul Fauziah (Biomedical Engineering, 2014)
Objective : This research was done  to measure the antioxidants and hypoglycemic activities of Nephelium lappaceum L. seed (NLS) extract and fractions. Methods: The ethanol extract of rambutan seeds were prepared by maseration method and the fractions (n-hexane, ethyl acetate, buthanol and water) by separation of extract based on the polarity. The antioxidant activity was determined by using  superoxide dismutase value (SOD), 1,1-diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging activity. The hypoglycemic activity was determined by using inhibition of α-glucosidase test. The DPPHscavenging and hypoglycemic activities were analized by median of Inhibitory Concentration (IC-50). Results: The highest SOD activity showed that ethyl acetate and aqueous fraction of NLS were 3.3771 µg/ml and 3.0374 µg/ml. Meanwhile DPPH assay showed that both NLS extract and fractions had low DPPH scavenging activity. Hypoglycemic activity showed that extract of NLS had highest activity as α-glucosidase inhibitor. Conclusion: Nephelium lappaceum L. seed extract and fractions have high SOD antioxidantvalue but low DPPH scavenging activity and can be used as potential hypoglycemic agent. Key Words: antidiabetic; antioxidants; α-glucosidase; hypoglycemic; scavenging